Science Process Skills Oriented E-LKPD Assisted by Liveworksheets on The Subject of Shifting Factors in Chemical Equilibrium - Rahmawati, Annisa Nur; Agustini, Rudiana (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This development research aims to describe the feasibility of electronic-based Learner Worksheets to train science process skills assisted by liveworksheets on the sub-matter of shifting factors in the direction of chemical equilibrium. E-LKPD feasibility in terms of validity, practicality, and effectiveness. This study used research and development (R&D) methods using the Borg & Gall model. This research is limited to limited trials. A limited trial was conducted at SMA Negeri 20 Surabaya on 27 students in class XI MIPA 6 who had previously received material on chemical equilibrium. E-LKPD, oriented to science process skills assisted by live worksheets, is declared feasible. When reviewed based on content and construct validity, Mode 5 is a very valid category. Based on student responses to the content, presentation, language, visuals, and science process skills criteria, the percentages for practicality were 93.1%, 83.72%, 95.07%, 95.07%, and 90.29%, respectively. Which is included in the very practical category, and is supported by the results of observations of relevant student activities that are more dominant than irrelevant activities. When viewed from the aspect of effectiveness, the results obtained based on the paired sample t-test values of pretest and posttest in the realm of science process skills show that tcount is 21.458, ttable is 1.706, and Sig. 0.000, This suggests that there are differences in the results of the pretest and posttest and is supported by the classical mastery of learning outcomes in the realm of knowledge of 92.59%.